Another attempt to adopt a machine for SHS lining ceramics inside pipes - Mahmoodian, R.; Rahbari, R.G.; Abd Shukor, Mohd Hamdi; Sparham, M. (Begell House, 2012)
In order to conduct centrifugal thermite research experiments in the laboratory, a special apparatus is required. A self-propagating high temperature synthesis machine with acceleration up to 350g was fabricated to accomplish experiments in laboratory settings. Then, thermite reaction of Ferro oxide III and Aluminium inside a pipe was performed to produce Alumina ceramic in the innermost layer and Ferro layer. Combustion synthesis is characterized by extreme heating rate, high temperature, and short reaction time. Centrifugal force facilitated the phase separation of multi-component products during the process. Preliminary tests were conducted prior to fabrication to realize reaction conditions.